Forecasting high-risk areas for dengue outbreaks in China: A trend analysis of Aedes albopictus and Aedes aegypti distributions from 2014 to 2030. - Yulun Xie; Bingbing Wang; Qi Chen; Hongjie Wei; Yanshu Ke; Fang Xie; Xuhua Guan; Jia Rui; Tianmu Chen (PLoS Neglected Tropical Diseases, 2025)
Background Global warming, urbanization and the resumption of global population movements post-COVID-19 have made the prevention and control of dengue and its vector transmission more challenging. To tackle this issue, this study evaluated and predicted the suitable habitats of Aedes albopictus and Aedes aegypti in China. This study aims to identify the key influencing factors, analyze patterns of habitat expansion and contraction, and explore regions in China at risk of dengue fever outbreaks in the future. Methodology/principal findings This study utilized mosquito distribution data from 2010 to 2023 and employed Maxent to map the distribution of suitable habitats. The key influencing factors and response curves were further analysed, and patterns of habitat expansion and contraction were investigated. The findings reveal that the main variables affecting the distributions of Ae. albopictus and Ae. aegypti are annual precipitation, annual mean temperature, and land use and land cover changes. The suitable habitat for Ae. albopictus shows a significant northward expansion trend, reaching large areas in Shandong and Henan province by 2030. The suitable habitat area for Ae. albopictus is increasing annually and can reach approximately 2.38 million square kilometers by 2030. Compared to the outbreak year of dengue fever in China in 2019, the suitable habitat area for Ae. albopictus in 2030 will increase by approximately 17.06%, with a growth of 2.57% in the sum of high-risk and medium-risk suitable habitat areas. In contrast, the suitable habitats of Ae. aegypti are primarily concentrated in Guangdong, Hainan and Yunnan Provinces. Conclusion/significance This study compared the potential changes in the distributions of suitable habitats for Ae. albopictus and Ae. aegypti in 2014, 2019, and 2023 and predicted suitable habitats for 2030, as well as contraction and expansion trends in the suitable habitats of Ae. albopictus. The findings aim to identify regions at risk of future dengue fever outbreaks in China, providing a scientific basis for public health authorities to develop effective dengue prevention and control strategies.